A Standardized Wedelia chinensis Extract Overcomes the Feedback Activation of HER2/3 Signaling upon Androgen-Ablation in Prostate Cancer - Tsai, Chin-Hsien; Tzeng, Sheue-Fen; Hsieh, Shih-Chuan; Tsai, Chia-Jui; Yang, Yu-Chih; Tsai, Mong-Hsun; Hsiao, Pei-Wen (Frontiers in Pharmacology, 2017)
Crosstalk between the androgen receptor (AR) and other signaling pathways in prostate cancer (PCa) severely affects the therapeutic outcome of hormonal therapy. Although anti-androgen therapy prolongs overall survival in PCa patients, resistance rapidly develops and is often associated with increased AR expression and upregulation of the HER2/3-AKT signaling pathway. However, single agent therapy targeting AR, HER2/3 or AKT usually fails due to the reciprocal feedback loop. Previously, we reported that wedelolactone, apigenin and luteolin are the active compounds in Wedelia chinensis herbal extract, and act synergistically to inhibit the AR activity in PCa. Here, we further demonstrated that an herbal extract of Wedelia chinensis (WCE) effectively disrupted the AR, HER2/3, and AKT signaling networks and therefore enhanced the therapeutic efficacy of androgen ablation in PCa. Furthermore, WCE remained effective in suppressing AR and HER2/3 signaling in an in vivo adapted castration-resistant PCa (CRPC) LNCaP cell model that was insensitive to androgen withdrawal and second-line antiandrogen, enzalutamide. This study provides preclinical evidence that the use of a defined, single plant-derived extract can augment the therapeutic efficacy of castration with significantly prolonged progression-free survival. These data also establish a solid basis for using WCE as a candidate agent in clinical studies.